La flûte pinkuyllu des Provincias Altas du Cuzco (Pérou) : organologie et symbolique érotique d’un aérophone andin - Raphaël Parejo-Coudert (Journal de la Société des Américanistes)
The pinkuyllu flute of the High Provinces of Cuzco (Peru): the organology and erotic symbolism of an Andean aerophone. The long recorder called the pinkuyllu, from the High Provinces of Cuzco (Peru), is an aerophone which has seldom been studied, and about which very little is known. In contrast to the incomplete, approximate and somewhat fanciful descriptions that exist elsewhere, this article presents the first organological and acoustic study of this instrument, based on exemplars in the author’s possession and on field recordings he has made. He analyses the instrument with reference to the agri-pastoral rituals to which it is linked. The author focuses on the flute’s erotic symbolism, and gives examples of its usage in Q’ellapampa, a rural community of the Kunturkanki district (in the Canas province of the Cuzco district, in Peru). He concludes with a review of aerophones of a similar type described by other authors in the southern region of Peru and Bolivia. A second article will seek to analyse the musical terminology of the pinkuyllu more precisely, along with the songs it accompanies.